Influence Leadership Transformational and Motivation Work on Employee Performance - Azizah Azizah (Yayasan Inovasi Akademi Nusantara, 2026)
This study aimed to analyze the effect of transformational leadership and work motivation on employee performance Batanghari University. Type of research is a quantitative survey research properties for descriptive purposes and an explanatory. Proportional sampling technique stratified random sampling. The sample of this study were employees of the University of Batanghari, amounting to 48 people. The data analysis technique used is multiple regression analysis using SPSS (Statistical Package for Social Science). The results of the study are: 1) The rate of respondents of 80.80% for transformational leadership often. To work motivation level of achievement of 73.65% of respondents included in the regular category. As for employee performance achievement level of 76.73% of respondents included in the category quite capable. There is the effect of transformational leadership and motivation to work together on employee performance at the University of Batanghari.